Reproductive Health CHOICES for Young Adults with Sickle Cell Disease or Trait: Randomized Controlled Trial Outcomes over Two Years. Issue 2 (28th August 2015) - Gallo, Agatha M.; Wilkie, Diana J.; Yao, Yingwei; Molokie, Robert E.; Stahl, Christiane; Hershberger, Patricia E.; Zhao, Zhongsheng; Suarez, Marie L.; Johnson, Bonnye; Angulo, Rigoberto; Carrasco, Jesus; Angulo, Veronica; et al.
Abstract: Interventions to assist reproductive health decision‐making in populations affected by sickle cell disease (SCD) or trait (SCT) lack proven efficacy over time. Our aim was to compare effects of CHOICES, a Web‐based multimedia education program on implementing informed reproductive plans, and usual care education (e‐Book) on reproductive knowledge, intention, and behavior over 24 months. We randomized 234 participants with SCD ( n = 138) or SCT ( n = 96) (age 18–35 years, 35 % male, 94 % African American) to CHOICES and e‐Book groups. Participants completed a sickle cell‐specific reproductive measure before and four times after the intervention (6, 12, 18 and 24 months). Compared to the e‐Book group the CHOICES group had significantly more improvement in knowledge over time ( p = .004) but not intention ( p = .18) or behavior ( p = .69). At baseline, 114 (48.7 %) participants reported having partners who would not put the couple at risk for their children inheriting SCD. Of the 116 (49.6 %) at ‐ risk participants, a higher poroportion of those who were in the CHOICES group chose partners that reduced their risk by the last visit than the e‐Book group ( p = .04). Study findings provide important insights for designing a national trial of the CHOICES intervention focusing on subjects whose partner status puts them at risk for having a child with SCD.